Analisis Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Dalam Meningkatkan Word Of Mouth Produk Sepeda Motor Honda Di Kecamatan Pelepat Kabupaten Bungo - Isman (Jurnal Ekonomi Manajemen, 2019)
ABSTRACT This study aims to see the effect of product influence on consumer satisfaction in increasing the promotion of Honda motorbikes in Pelepat District, Bungo Regency. The population in this study may be 3922 respondents and the sample may be 98 respondents. The sampling technique was purposive sampling. Based on the results of the calculation of the significance of each path, it shows the t-count value of the product quality variable (X) = 12.066 and customer satisfaction (Y1) is greater than t-table = 1.982 and the significance value (α) = 0.000 is smaller the significance value (α) ) = 0.05 so that it can be stated that it can be stated that each pathway has a significant effect, both the effect of product quality (X) on customer satisfaction (Y1) and the effect of customer satisfaction (Y1) on the Word of Mouth (Y2). While the results of the path calculation indirectly show that the effect of product quality (X) on Word of Mouth (Y2) through customer satisfaction (Y1) is = 0.776 x 0.624 = 0.484 that the effect of product quality can increase word of mouth mediated by consumer satisfaction with the product. Honda motorbikes in Pelepat District, Bungo Regency, amounting to 0.484.